Consequences of 'tiger' parenting: a cross‐cultural study of maternal psychological control and children's cortisol stress response. Issue 3 (4th May 2016) - Doan, Stacey N.; Tardif, Twila; Miller, Alison; Olson, Sheryl; Kessler, Daniel; Felt, Barbara; Wang, Li
Abstract: Parenting strategies involving psychological control are associated with increased adjustment problems in children. However, no research has examined the extent to which culture and psychological control predict children's stress physiology. We examine cultural differences in maternal psychological control and its associations with children's cortisol. Chinese ( N = 59) and American ( N = 45) mother‐child dyads participated in the study. Mothers reported on psychological control. Children's cortisol was collected during a stressor and two indices of Area Under the Curve (AUC) were computed: AUCg which accounts for total output, and AUCi, which captures reactivity. Results indicate that Chinese mothers reported higher levels of psychological control and Chinese children had higher levels of AUCg than their American counterparts. Across both cultures, psychological control was significantly associated with increased cortisol levels as indexed by AUCg. There were no associations for AUCi. Finally, mediation analyses demonstrated that psychological control fully explained cultural differences in children's cortisol stress response as indexed by AUCg. Abstract : Maternal psychological control mediates cultural differences in children's cortisol stress response.